PENGARUH KETEPATAN ANGGARAN DAN PENGENDALIAN MANAJERIAL SEKTOR PUBLIK PADA AKUNTABILITAS KINERJA SKPD - Pradnya Dewi, Made Astari; Supadmi, Ni Luh (E-Jurnal Akuntansi, 2015)
Accountability performance is a performance accountability to various stakeholders such as local government and the wider community. This has an impact on the support elements for performance accountability. The purpose of this study was to examined the influence of the accuracy of the budget and managerial control of the accountability of public sector performance. This research was conducted in the city of Denpasar SKPD of 33 SKPD with the method of data collection used the questionnaire technique. The number of samples taken an overall total of 33 SKPD SKPD the total sample method. Technique multiple linear regression analysis used in study. The results show the accuracy of the budget and managerial control of the public sector is a significant positive effect on performance accountability. This proves that the better the accuracy of the budget and managerial control of the public sector , the better accountability of local government performance .
Keywords: accuracy of the budget, managerial control, accountability performance